1966
DOI: 10.1071/bi9661017
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Surface Wax Deposits on Apple Fruit

Abstract: SummaryOptical and electron micrographs of surface wax deposits on four varieties show varietal differences. In addition to normal structure a lath·like wax can be seen in the fine cuticle cracks that are plentiful on Golden Delicious and sparse on other varieties; another form of wax is always at right angles to abrasion marks on the fruit and is present on all varieties.The removal of surface wax by solvents exposes a cuticle structure which is related to the deposits and differs in some varieties. The ease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1967
1967
1995
1995

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…However, according to Fitter and Hay (1981), the rate of cuticular transpiration in plants depends upon the thickness, continuity and composition of the cuticle. Furthermore Hall (1966) found that removal of wax from apple fruits by any method caused an increase in transpiration rate. Our observations on AS.…”
Section: Cuticular Transpirationmentioning
confidence: 99%
“…However, according to Fitter and Hay (1981), the rate of cuticular transpiration in plants depends upon the thickness, continuity and composition of the cuticle. Furthermore Hall (1966) found that removal of wax from apple fruits by any method caused an increase in transpiration rate. Our observations on AS.…”
Section: Cuticular Transpirationmentioning
confidence: 99%
“…Numerous modifications for improving the preparation of heavy metal shadowed carbon replicas from plant tissue surfaces for examination in the transmission electron microscope have been described (e.g., 1,5,10,11,13,38) since the introduction of this approach by JUNIPER and BRADLEY in 1958 (17). In addition, we are aware of two laboratories that have described the successful preparation of platinum shadowed replicas at room temperature (1,2,28,37).…”
Section: The Direct Platinum Shadowed Replica Techniquementioning
confidence: 99%
“…For example. Hall (1966) found that the removal of wax from the fruit of apples increased the rate at which they transpired. Gmcarevic and Radler (1971) stated that careful removal of the surface wax of grapes was almost as effective as peeling in promoting water evaporation.…”
mentioning
confidence: 99%